Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00268-018-4575-0
|View full text |Cite
|
Sign up to set email alerts
|

Changing Profile of Primary Hyperparathyroidism Over Two and Half Decades: A Study in Tertiary Referral Center of North India

Abstract: Our study reveals a change in trend in PHPT which is similar to evolution of this disease in western population and positively corroborated with observations from China, Hong Kong and Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
(46 reference statements)
4
19
0
Order By: Relevance
“…While the developed world focused on laying guidelines for filtering out cases of asymptomatic PHPT for surgical intervention and promoting minimal access surgery with the aid of newer diagnostic and localization tools, the developing world was observing a change in disease spectrum from advanced symptomatic to lesser degree of symptomatic disease and a reduction in incidence of associated Vitamin D deficiency. Some authors from developing countries have focused on the changing clinical spectrum of PHPT (6)(7)(8)(9)(10) and suggested that the trajectory of the change is similar to what was observed in developed countries a few decades earlier. We observed these dramatic changes in disease epidemiology and sought to review and address the question that whether the epidemiology of this disease continues to differ from the developed countries?…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…While the developed world focused on laying guidelines for filtering out cases of asymptomatic PHPT for surgical intervention and promoting minimal access surgery with the aid of newer diagnostic and localization tools, the developing world was observing a change in disease spectrum from advanced symptomatic to lesser degree of symptomatic disease and a reduction in incidence of associated Vitamin D deficiency. Some authors from developing countries have focused on the changing clinical spectrum of PHPT (6)(7)(8)(9)(10) and suggested that the trajectory of the change is similar to what was observed in developed countries a few decades earlier. We observed these dramatic changes in disease epidemiology and sought to review and address the question that whether the epidemiology of this disease continues to differ from the developed countries?…”
Section: Introductionmentioning
confidence: 88%
“…Yadav and cols. grouped the PHPT patients into three subgroups based on the time span; 1990-1999, 2000-2009, 2010-2016, and clinical and biochemical parameters were compared (10). The clinical presentation in this study has evolved progressively with increase in older age group (35 vs 39 vs 43.85, p < 0.001), less patients with musculoskeletal symptoms (85.3 vs 76.8 vs 61%, p = 0.002) and less patients with severe bone disease (29.4 vs 10.7 vs 10.7%, p = 0.088).…”
Section: Changing Epidemiologymentioning
confidence: 99%
“…The main contributing factor to the shift in the clinical presentation of pHPT is probably an iceberg phenomenon with a higher detection rate of patients affected. Studies from China, India and Brazil, amongst other countries, still show a dominant percentage of pHPT patients with classic symptoms and more severe biochemical abnormalities but the differences are being levelled out . Access to biochemical screening of calcium levels seems to be the crucial factor.…”
Section: Evolving Concepts Of Primary Hyperthyroidismmentioning
confidence: 99%
“…[27282930] Most of these studies are from developed countries where the clinical profile of PHPT patients is totally different[31] as compared to developing world. Although clinical profile of PHPT is changing in the developing world[19] but it continues to be a symptomatic disorder with skeletal, renal and metabolic complications at a much younger age. [31821222332333435] Most of the studies demonstrating non-superiority of CPTx over FPTx have been done in a patient population where the majority of the cases are asymptomatic screen detected PHPT.…”
Section: Discussionmentioning
confidence: 99%
“…This was a retrospective study of all PHPT patients treated in the Department of Endocrine surgery, SGPGIMS, Lucknow between January 1990 to December 2017. The evaluation and diagnostic protocol at our institute has been published in our previous publications[31819] and [Doc S1]. The patient cohort was divided into 2 groups, based on operative approach (CPTx vs FPTx) or use of IOPTH (Intraoperative parathyroid harmone monitoring) vs. no use of IOPTH.…”
Section: Methodsmentioning
confidence: 99%